2005
DOI: 10.1088/0953-8984/17/43/016
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electric field gradient in LaCoO3perovskite investigated by perturbed angular correlation spectroscopy

Abstract: The time differential perturbed angular correlation (TDPAC) technique was used to study the temperature dependence of electric field gradient (EFG) in LaCoO 3 perovskite using 111 In → 111 Cd and 181 Hf → 181 Ta nuclear probes. The radioactive parent nuclei 111 In and 181 Hf were introduced into the oxide lattice through a chemical process during sample preparation and were found to occupy only the Co sites in LaCoO 3 . The PAC measurements with 111 Cd and 181 Ta probes were made in the temperature range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
8
0
5
Order By: Relevance
“…These discontinuities are seen more clearly for the data taken with 111 Cd probe at Co sites. Similar discontinuities were also observed in PAC measurements in LaCoO 3 [4] and were attributed to thermally induced spin state transition in Co atoms from low-spin (LS) nonmagnetic state (t 6 2g e 0 g ) to an intermediate-spin (IS) state (t 5 2g e 1 g ) and then from the intermediate-spin (IS) state to high-spin (HS) state (t 4 2g e 2 g )respectively. In the present case transition from LS or IS state to HS state was observed in a wide Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…These discontinuities are seen more clearly for the data taken with 111 Cd probe at Co sites. Similar discontinuities were also observed in PAC measurements in LaCoO 3 [4] and were attributed to thermally induced spin state transition in Co atoms from low-spin (LS) nonmagnetic state (t 6 2g e 0 g ) to an intermediate-spin (IS) state (t 5 2g e 1 g ) and then from the intermediate-spin (IS) state to high-spin (HS) state (t 4 2g e 2 g )respectively. In the present case transition from LS or IS state to HS state was observed in a wide Fig.…”
Section: Resultssupporting
confidence: 76%
“…The observed quadrupole frequencies at 77 K ν Q = 133(1) MHz (η = 0.14) and ν Q = 44.4(4) MHz (η = 0.47) were associated to 111 Cd probe nuclei at Tb and Co sites, respectively. This assignment is based on results of previous PAC results for several rare-earth perovskites [4,6,8]. The measurements with 181 Ta probe showed a single fraction with well-resolved quadrupole interaction, which was associated to 181 Ta at Co sites.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…These interactions were assigned to 181 Ta probe nuclei occupying Cr(Fe) sites. The assignments are based on evidence obtained from previous PAC studies of LaCrO 3 and LaFeO 3 and LaMnO 3 [5,6]. From the results of magnetic interactions in LaCrO 3 , LaFeO 3 it was concluded that the spin density transferred from the nearest Cr 3+ (Fe 3+ )ions to rare-earth sites in super exchange interaction should be much smaller than to Cr or Fe sites.…”
Section: Compoundmentioning
confidence: 86%
“…These interactions were attributed to 181 Ta probe nuclei occupying Cr sites. The assignment is based on the evidence obtained in a previous PAC study of La(Cr,Fe,Mn)O 3 perovskites [7,8]. From the magnetic interactions observed in La(Cr,Fe)O 3 it was concluded that the spin density transferred from the nearest Cr 3+ (Fe 3+ ) ions to rare-earth atom site via oxygen orbital in super exchange interaction is much smaller compared to the Cr or Fe sites.…”
Section: Resultsmentioning
confidence: 88%